A Final Formality: Three Modernist Pavilion Houses of the early 1960s - Dudding, Michael (Architectural History Aotearoa, 2005)
The Beard, Alington, and Mackay houses represent the endpoint of a direction in New Zealand domestic architecture that was both internationalist and based within the realities of local house building in the mid-twentieth century. Imi Porsolt, while reviewing Stephanie Bonny and Marilyn Reynolds'book Living with 50 Architects in 1980, specifically points to the Alington house as the final formalisation of this purist trend. Porsolt's review provides an historical subtext to Living with 50 Architects that opposes the "altogether austere style" of the pavilion with the vernacularism of what is best described as the "elegant shed" tradition of New Zealand house design. More elegant than the elegant shed, these pavilions reveal something of a "blind spot" in New Zealand's architectural history – aside from the inclusion of the Beard and Alington houses in Living with 50 Architects,they have not appeared in any of the canon-forming historical surveys such as Mitchell and Chaplin's The Elegant Shed or Shaw's A History of New Zealand Architecture. The Mackay house also has not featured until its recent appearance in Lloyd Jenkins' At Home: A Century of New Zealand Design. This paper uses Porsolt's view as a useful starting point from which to consider the relationship that exists between the Beard, Alington, and Mackay houses, and their place in the development of New Zealand's domestic architecture during the 1960s.